Contemporary Teaching and Learning Strategies for Future Competencies - Tomičić Furjan, Martina; Hrustek, Larisa; Tomičić-Pupek, Katarina (9th FEB International Scientific Conference: Sustainable Management in the Age of ESG and AI: Navigating Challenges and Opportunities, 2025)
When service learning meets sustainability learning, new integration benefits arise within curricular and extracurricular activities in higher education. By exploring the approach of integrating service and sustainability learning, their potential to enhance student engagement and foster a sustainability culture is revealed. Active learning methodologies, which include digital technology inspired innovations with problem-based learning and community engagement, offer to significantly improve students' understanding of sustainability while developing competencies for future careers. Importance of hybrid pedagogies that intertwine service and sustainability learning with traditionally introduced academic content form contemporary teaching and learning strategies, demonstrating their positive impact on students’ engagement and sense of affiliation to community while contributing to building a resilient and sustainable environment. Additionally, the role of extracurricular activities in promoting entrepreneurship as a self-transcendence, self-efficacy and desirable business behaviour among students is evident, illustrating how such activities can enhance their competencies. The need for educators to adopt facilitative roles in creating supportive learning environments by advocating for professional development and fostering teachers to effectively implement these contemporary teaching strategies is explored as well. This paper aims to provide a conceptual framework for integrating service and sustainability learning into educational practices, thereby preparing students to tackle complex sustainability challenges.